Políticas tributárias e a informalidade urbana: efeitos e desafios do Simples Nacional - Anita Carmela Militao de Pascali (2018)
The Brazilian labor market is known for its high rates of informality. Given this, governments have sought to implement actions that would reduce such expressive numbers. The National Statute of Microenterprise and Small Business, implemented with the National Simple, can be considered one of the main attempts to address this challenge. This statute also created the figure of the Individual Microentrepreneur, reducing costs and providing benefits for their formalization. The purpose of this work is to verify if the social cost involved in the National Simple corresponds to the effectiveness of the measure, based on the investigation of the main motivations for informality and the choice of self-employed workers to formalize their activities. To do so, this work discusses the concepts of informality, estimates its size in the Brazilian economic scenario and reviews its causes and consequences. In a second moment, it analyzes the impact of the Simple, main public policy implemented with the aim of reducing informality. From the classification of the Simple as an inductive tax norm, it is evident that this policy cannot be defined only by its cause, but also by its effects in the market, since the induction of behaviors is part of its own nature.